Penerapan Model Pembelajaran Certainly of Response Index untuk Meningkatkan Aktivitas dan Hasil Belajar Pada Materi Perusahaan Jasa - Yanti, Syafridha (Jumper: Journal of Educational Multidisciplinary Research, 2024)
The problem in this research is the low activity and learning outcomes of students in accounting subjects where the majority of students still experience difficulties in understanding the recording of service company accounting cycles. The aim of this research is to increase learning activities and accounting learning outcomes by implementing the Certainty of Response Index learning model. This research was carried out at SMA Negeri 4 Takengon and the subjects in this research were class XI IPS students at SMA Negeri 4 Takengon, totaling 31 people. The technique used to collect data in this research uses tests and observations. The test used is an essay test taken from the student's textbook. Observations of student learning activities are carried out directly during the teaching and learning process by applying the Certainty of Response Index learning model. From the results of the analysis, pretest data was obtained as a result of students' initial learning with 38.71% completed with an average student score of 60.16. Cycle I post-test data with an average score of 64.35 with 48.39% of students meeting the requirements. Meanwhile, the second cycle post-test data showed an average student learning outcome score of 76.78 with 83.87% of students achieving the Minimum Completeness Criteria (KKM). This shows that there is an increase in student learning outcomes from posttest cycle I to posttest cycle II by 35.48%. The results of observations that have been made show an increase in student activity of 41.93%, where in the first cycle it was 54.84% while in the second cycle it was 96.77%. It can be concluded that the application of the Certainty of Response Index learning model in class XI IPS SMA Negeri 4 Takengon T.P. 2022/2023 can improve learning activities and student learning outcomes.